Evaluation of Questioned Document Examination of 780 Cases Trabzon 2007-2013 - Okumuş, Hasan; Kırcı, Güven Seçkin; Aydoğdu, Halil İlhan and Birincioğlu, İsmail and Özer, Erdal (The Bulletin of Legal Medicine, 2016)
Handwriting and signatures are result of a complex series of neurological, anatomical and physiological systems in the human body’s and also they are important parameters and still maintains its topicality in determining identity. Scientific examination of the Handwriting and/or signatures are nearly 100 years integral part of forensic science. In this study we evaluated expert examination which were conducted on expert forensic document files in Trabzon province. In this study 780 cases were evaluated according to Judicial authorities, document numbers, types, questions, delivery times. As a result, many difficulties were experienced in our country such as inadequate experienced experts lack of laboratories, inadequate comparable samples and lack of specific format or standards of documents. In these kinds of works experts must work seriously and standardization of the documents must be ensured. Key words: Handwriting, Signature, Questioned Documents, Trabzon